Laparoscopic wedge resection and omental patch in an elderly patient with acute abdomen: a case report - Parham Khoshdani Farahani (Journal of Medical Case Reports)
Abstract Background Perforated gastric ulcers represent life-threatening surgical emergencies with particularly high morbidity and mortality in elderly patients. While omental patch repair remains the standard treatment for duodenal perforations, optimal management of complex gastric perforations, especially those with necrosis or concurrent lesions, remains controversial. Case presentation We present the case of a 72-year-old Iranian woman with multiple comorbidities who presented with septic shock secondary to gastric perforation. Diagnostic laparoscopy revealed a 1.5-cm perforation with surrounding necrosis and an adjacent gastric polyp. The patient successfully underwent combined laparoscopic wedge resection and omental patch repair, demonstrating the feasibility of this minimally invasive approach in high-risk patients. The procedure included complete excision of necrotic tissue and polyp with stapled wedge resection, followed by reinforcement using a vascularized omental patch. Postoperative recovery was uneventful, with the patient discharged on day 10. Histopathology confirmed benign ulceration without malignancy. At the 3-month follow-up, the patient remained asymptomatic with no recurrence. Conclusion This case highlights that laparoscopic wedge resection with omental patch repair offers both diagnostic and therapeutic advantages for complex gastric perforations, particularly when tissue viability is questionable or concurrent lesions are present. The technique combines the benefits of minimally invasive surgery, reduced morbidity, and faster recovery with the reliability of traditional omental patching. The successful outcome highlights the expanding role of laparoscopy in emergency general surgery for high-risk populations.